Assumptions of the future of artificial intelligence in Tanzania academic libraries: A review of literature - Mwilongo, Kardo Joseph; Mwageni, Rhodes (Dar es Salaam University Press (DUP), 2024)
A conference paper submitted to the 4th COTUL Scientific conference of 7th to 11th November 2022 Institute of Accountancy Arusha (IAA), Arusha.